N-Heterocyclic carbene catalyzed esterification of aromatic aldehydes with alcohols under aerobic conditions - Kiran, I. N. Chaithanya; Lalwani, Komal G.; Sudalai, Arumugam (RSC Advances, 2013)
A simple, organocatalytic procedure for the direct oxidative esterification of a variety of aromatic aldehydes with alcohols has been described that affords the corresponding aromatic esters in high yields. The method employs N-heterocyclic carbenes as catalysts and molecular O-2 as an oxidant under ambient conditions.